Abscisic acid‐dependent histone demethylation during postgermination growth arrest in Arabidopsis. (12th April 2019) - Wu, Jinfeng; Ichihashi, Yasunori; Suzuki, Takamasa; Shibata, Arisa; Shirasu, Ken; Yamaguchi, Nobutoshi; Ito, Toshiro
Abstract: After germination, seedlings undergo growth arrest in response to unfavourable conditions, a critical adaptation enabling plants to survive harsh environments. The plant hormone abscisic acid (ABA) plays a key role in this arrest. To arrest growth, ABA‐dependent transcription factors change gene expression patterns in a flexible and reversible manner. Although the control of gene expression has important roles in growth arrest, the epigenetic mechanisms in the response to ABA are not fully understood. Here, we show that the histone demethylases JUMONJI‐C domain‐containing protein 30 (JMJ30) and JMJ32 control ABA‐mediated growth arrest in Arabidopsis thaliana . During the postgermination stage (2–3 days after germination), the ABA‐dependent transcription factor ABA‐insensitive3 (ABI3) activates the expression of JMJ30 in response to ABA. JMJ30 then removes a repressive histone mark, H3 lysine 27 trimethylation (H3K27me3), from the SNF1‐related protein kinase 2.8 ( SnRK2.8 ) promoter, and hence activates SnRK2.8 expression. SnRK2.8 encodes a kinase that activates ABI3 and is responsible for JMJ30‐ and JMJ32‐mediated growth arrest. A feed‐forward loop involving the ABI3 transcription factor, JMJ histone demethylases, and the SnRK2.8 kinase fine‐tunes ABA‐dependent growth arrest in the postgermination phase. Our findings highlight the importance of the histone demethylases in mediating adaptation of plants to the environment. Abstract : The histone demethylases JMJ30 and JMJ32 regulate the tolerance programme for ABA‐mediated growth arrest in Arabidopsis .